Persepsi Menganut Islam dan Kebudayaan dalam Kajian Sejarah Peradaban Islam - Nasution, Abdul Ghani Jamora; Harahap, Irma Sari; Hutajulu, Mutika Amalia Amini; Amalia, Suci (Al-DYAS, 2023)
This paper discusses about Islam and culture. Islam basically has two terms i.e. religious and cultural. There is no distinguishing gap between “religion of Islam” and “Islamic culture”. In the scientific perspective, the two can be differentiated, but in view of Islam itself it cannot be separated. Both form integration. The integration is so tight. Therefore, it is often difficult to distinguish whether the religion or culture; for example, marriage, divorce, reconciliation and inheritance. In the perspective of culture, it makes matters of culture; yet, their provision comes from God. History has been a witness to the great building of Islamic civilization pioneered by the Prophet (s), until it continued during the time of Khulafaurasyidin, Umayyad Caliphate and Abbasids. This research aimed to see a portrait of Islamic civilization from the Prophet (s) to the Abbasids, especially in the study of the heritage of values and concepts that mark the majesty of that civilization and the opportunity of Indonesia as a unity of the nation and the state in modeling, following and implementing the values and concepts of Islamic civilization in order to build its civilization in the future. This research used a qualitative approach with library research type and content analysis technique. In addition, historical approaches are applied for the deepening of study. The results showed that the heritage of Islamic civilization in the time of the Prophet(s), Khulafaurasyidin, Umayyad and Abbasid Caliphate that brought religious values and concepts (tawhid), socio-cultural, legal, political, and science had a great opportunity to bring Indonesia to a great civilization. Since long ago, there hasbeen cultural acculturation between Islamic teachings and Sharia with Indonesian culture, not exception to aspects of language, customs, traditions, and legal systems (legislation) in various ethnic groups in the archipelago (Nusantara). Therefore, in order to become a superior nation and have a high civilization in leading the world, both in the fields of religion, social, cultural, legal, political and also science, the future construction of Indonesia should take lessons from the legacy of Islamic civilization in the time of the Prophet(s), Khulafaurasyidin, Umayyad and Abbasids Caliphate.